Laparoscopic treatment of retroperitoneal cystic mesothelioma. Two cases reported - Morales Artero, Sonia (Int J Surg Case Rep, 2016)
Retroperitoneal cystic mesothelioma is a very rare lesion. The pathogeny is unclear and establishing a preoperative diagnosis versus others retroperitoneal cystic lesions is difficult. Thus, with increasing experience in laparoscopic retroperitoneal surgery, the use of this approach for exploration of a retroperitoneal mass of unknown origin may provide an alternative to classic open surgery and all the benefits of laparoscopy. We present two cases treated laparoscopycally and review the literature.